2016
DOI: 10.3945/jn.115.227264
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood ω-3 Fatty Acids Are Inversely Associated with Carotid Intima-Media Thickness in Indigenous Mexican Women

Abstract: Overall, circulating n-3 PUFAs were not associated with IMT. However, we observed a strong statistically significant inverse association with IMT in indigenous Mexican women. Future studies should evaluate genetic markers that may reflect differences in n-3 PUFA metabolism across populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…EPA, and DHA, suggesting good reproducibility of these PUFA in DBS samples. Ease of collection, storage, and analysis of DBS allows for larger clinical studies (Bisgaard et al, 2016;Collins et al, 2017;Monge et al, 2016) and cross-sectional studies (Adjepong et al, 2018;Mashavave et al, 2016) to utilize DBS for determining n-3 PUFA status, and our results allow comparison of EPA + DHA levels between such studies and ultimately populations with confidence. Because research interests of the five labs included in this study are primarily focused on PUFA, reproducibility of ARA, EPA, and DHA may be better compared to labs with greater interest in other fatty acids.…”
Section: Resultsmentioning
confidence: 89%
“…EPA, and DHA, suggesting good reproducibility of these PUFA in DBS samples. Ease of collection, storage, and analysis of DBS allows for larger clinical studies (Bisgaard et al, 2016;Collins et al, 2017;Monge et al, 2016) and cross-sectional studies (Adjepong et al, 2018;Mashavave et al, 2016) to utilize DBS for determining n-3 PUFA status, and our results allow comparison of EPA + DHA levels between such studies and ultimately populations with confidence. Because research interests of the five labs included in this study are primarily focused on PUFA, reproducibility of ARA, EPA, and DHA may be better compared to labs with greater interest in other fatty acids.…”
Section: Resultsmentioning
confidence: 89%
“…Because of their favourable effect on cardiometabolic risk factors, the omega-3 index (defining the amount of EPA and DHA as a proportion of total fatty acids in red blood cells) has been proposed as a biomarker for assessing the risk of coronary heart disease [ 70 ]. This is plausible considering that the omega-3 index in red blood cells is thought to be representative of cardiac cell membranes [ 71 ] and was found to be inversely associated with the risk of morbidity [ 72 , 73 ] and mortality from coronary heart disease [ 74 , 75 , 76 ]. Interestingly, Allaire et al reported a greater increase in the omega-3 index following DHA supplementation compared with EPA supplementation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 index is inversely associated with a number of cardiovascular risk factors and with cardiovascular morbidity (36,37) and mortality (38,39). Harris and von Schacky (34) suggest than an omega-3 index of or more is associated with optimal cardioprotection.…”
Section: Discussionmentioning
confidence: 99%